2015
DOI: 10.1007/s12035-015-9099-0
|View full text |Cite
|
Sign up to set email alerts
|

High Serum MiR-130a Levels Are Associated with Severe Perihematomal Edema and Predict Adverse Outcome in Acute ICH

Abstract: The development and/or progression of perihematomal edema (PHE) in patients with acute spontaneous intracerebral hemorrhage (ICH) vary substantially with different individuals. Although hematoma volume is a useful indicator for predicting PHE, its predictive power was not good at the early stage of ICH. Better predictors are urgently needed. In this study, we found that miR-130a was elevated in the serum of ICH patients and was an independent indicator positively associated with PHE volume within the first 3 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 41 publications
2
49
0
Order By: Relevance
“…RNA extraction and real‐time quantitative PCR (qPCR) were performed to evaluate the expression of miRNAs as previously reported (14). Total miRNAs from brain tissue, microvessels, or cells (BMEC, astrocytes, and pericytes) were extracted by using mirVana PARISTM RNA isolation kit according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…RNA extraction and real‐time quantitative PCR (qPCR) were performed to evaluate the expression of miRNAs as previously reported (14). Total miRNAs from brain tissue, microvessels, or cells (BMEC, astrocytes, and pericytes) were extracted by using mirVana PARISTM RNA isolation kit according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Increased levels of circulating miRNAs like miR-522, miR-122, and miR-29c were observed in the plasma of ICH patients with hematoma compared to ICH patients without hematoma (Zheng et al, 2012). Blood miRNA profiling also indicated the possibility of identifying perihematoma edema (PHE) after ICH in both humans and rats (Zhu et al, 2015; Wang et al, 2016a). A correlation was observed between miR-126 levels in blood and the PHE volume in ICH patients (Zhu et al, 2015).…”
Section: Micrornas As Stroke Biomarkersmentioning
confidence: 99%
“…A correlation was observed between miR-126 levels in blood and the PHE volume in ICH patients (Zhu et al, 2015). The rat model of ICH indicated that increased levels of miR-29c and miR-122 in plasma correlates with PHE formation (Wang et al, 2016a). Rupture of intracranial aneurysms (IAs) is a major cause of hemorrhagic stroke, especially SAH (Krings et al, 2011).…”
Section: Micrornas As Stroke Biomarkersmentioning
confidence: 99%
“…Cavtratin decreases eNOS activity by mimicking the CAV1 inhibitory clamp (Figure 2B) and does not affect the function of other NOSs in vivo and targets eNOS to a significant extent 53 . Cavtratin reduces microvascular hyperpermeability and blocks tumor progression 52, 54 , restores tight junctions in C-C motif chemokine 2 (CCL2) treated brain microvascular endothelial cells (BMECs) 55 , inhibits matrix metalloproteinase-2/9 (MMP2/9) and cyclooxygenase-2 (COX2), which could lead to stabilization of atherosclerotic plaques and protective effects for intracerebral hemorrhages 56, 57 . Cavtratin also diminishes glia cell growth 58 and protects the blood-brain-barrier (BBB), when treated with vascular endothelial growth factor A (VEGF-A) in a mouse model of multiple sclerosis (MS) 59 .…”
Section: Novel Modulators Of the No-nosgc-cgmp Pathwaymentioning
confidence: 99%